Selective Reduction of Iron from Iron–Manganese Ore of the Keregetas Deposit Using Hydrogen - Nurlybai Kosdauletov; Assylbek Nurumgaliyev; Bakyt Zhautikov; Bakyt Suleimen; Galymzhan Adilov; Bauyrzhan Kelamanov; Konstantin Smirnov; Talgat Zhuniskaliyev; Yerbol Kuatbay; Gulzat Bulekova; Assylbek Abdirashit (Metals)
This study presents the results of the solid-state reduction of iron–manganese ore from the Keregetas deposit (Kazakhstan) using hydrogen as a reductant. The findings demonstrate that hydrogen is an effective and environmentally friendly reducing agent, enabling selective reduction of iron. The investigated iron–manganese ore exhibits a complex mineralogical composition comprising oxides of Fe, Mn, Si, and aluminosilicate complex phases. X-ray diffraction (XRD) analysis of the raw ore confirmed the presence of goethite, hematite, quartzite, and MnO2 as the primary mineral phases. Oxidative roasting induced the dehydration of goethite and its conversion to hematite, along with the formation of Mn2O3 and Mn3O4 phases. The detection of Mn7SiO12 indicates interaction between manganese and silica under high-temperature oxidation conditions. Reduction experiments were conducted in an RB Automazione MM 6000 laboratory furnace at temperatures ranging from 700 to 1100 °C, with a holding time of 60 min and a hydrogen flow rate of 0.5 L/min. Results revealed high selectivity of hydrogen reduction: at 700–800 °C, iron and arsenic were predominantly reduced, as evidenced by the emergence of a metallic Fe-containing phase, while oxides of Mn, Si, Ba, and Al remained in the residue. Increasing the temperature to 900–1000 °C resulted in partial reduction of manganese. At 1100 °C, a decrease in the intensity of the metallic phase was observed, likely due to sintering of ore particles and reduced gas permeability. The reduced metal and oxides were readily separable by melting. These findings provide a basis for developing processing schemes for beneficiation and hydrometallurgical treatment of iron–manganese ores from Kazakhstan.